2002
DOI: 10.1177/1073858402238515
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: GABA and Glutamate in the Human Brain

Abstract: Cortical excitability reflects a balance between excitation and inhibition. Glutamate is the main excitatory and GABA the main inhibitory neurotransmitter in the mammalian cortex. Changes in glutamate and GABA metabolism may play important roles in the control of cortical excitability. Glutamate is the metabolic precursor of GABA, which can be recycled through the tricarboxylic acid cycle to synthesize glutamate. GABA synthesis is unique among neurotransmitters, having two separate isoforms of the rate-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
429
1
17

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(455 citation statements)
references
References 87 publications
8
429
1
17
Order By: Relevance
“…However, what may be the function of increasing glutamate and glutamine? Glutamine is the metabolic precursor of glutamate in the mammalian brain (Petroff, 2002). After synaptic transmission of glutamate, surrounding glia cells metabolize glutamate to glutamine, which is in turn transported to the neurons were it is synthesized to glutamate (Petroff, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, what may be the function of increasing glutamate and glutamine? Glutamine is the metabolic precursor of glutamate in the mammalian brain (Petroff, 2002). After synaptic transmission of glutamate, surrounding glia cells metabolize glutamate to glutamine, which is in turn transported to the neurons were it is synthesized to glutamate (Petroff, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Putrescine can be converted to GABA through an acetylated intermediate while glutamate is capable of modification to ornithine, the precursor of putrescine. 27 Changes in levels of polyamines induced by misexpression of their biosynthetic and catabolic enzymes may therefore confer a reduced neuroprotective capacity to states of oxygen deprivation or metabolic stress in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…95 Inhibitory neurotransmission in the mammalian brain is mainly accomplished by gabaergic neurons, responsible for the release of GABA. 96 GABA neurotransmission modulates the activity of noradrenergic, dopaminergic and serotonergic systems. 96 Clinical data have pointed to an alteration in gabaergic neurotransmission in mood disorders and more specifically in major depression.…”
Section: Discussionmentioning
confidence: 99%
“…96 GABA neurotransmission modulates the activity of noradrenergic, dopaminergic and serotonergic systems. 96 Clinical data have pointed to an alteration in gabaergic neurotransmission in mood disorders and more specifically in major depression. 97 Thus, cerebrospinal fluid and plasma studies have observed altered levels of GABA in depressed patients.…”
Section: Discussionmentioning
confidence: 99%